Environmental enrichment preconditioning prevents chronic social defeat stress-induced memory impairment and hippocampal neurodegeneration - Nik Ramli, Nik Nasihah; Shamsul Adzmi, Nur Adzreen; Nasarudin, Siti Nur Atiqah Zulaikah; Hashim, Mohamad Hisham (University of Malaya, 2024)
The World Health Organization anticipated major depressive disorder to become the primary contributor to the global burden of disease by 2023. Chronic psychological stress directly impacts synaptic plasticity and the formation of stress-associated memories, contributing to a predisposition to depression. Conversely, research suggests that environmental enrichment, promoting physical activity, social interaction, and sensory stimulation, positively influences neurocognitive functions. However, there is a paucity of studies examining the effects of environmental enrichment on learning and memory in chronic social defeat stress (CSDS) models. Male C57BL/6N mice were (n=5) housed in enriched environments for 30 days before undergoing daily social defeat stress by ICR strain aggressor mice over 10 days. Depressive-like behavior was assessed using the forced swim test (FST) and tail suspension test (TST). Memory and learning functions were evaluated through the Y-maze and novel object recognition (NOR) tests. Brain tissues were subjected to Hematoxylin and Eosin staining to examine histological alterations in the hippocampal region. Environmental enrichment significantly alleviated depressive-like behavior in mice subjected to CSDS. Dysfunctions in spatial working memory and recognition memory as well as hippocampal degeneration induced by CSDS were notably improved in mice exposed to environmental enrichment as compared to those without exposure. This study highlights the significance of environmental enrichment preconditioning in ameliorating memory and learning impairments induced by CSDS.